Mitochondrial ROS and cancer drug resistance: Implications for therapy - Okon, Imoh S. (Pharmacol Res, 2015)
Under physiological conditions, a well-coordinated and balanced redox system exists to ensure that reactive oxygen species (ROS) are appropriately utilized to accomplish specific functions, such as signaling and protein regulation. The influence of ROS within malignant cells, whether for good or bad may depend on several factors, such as tumor and tissue type, disease stage, treatment strategy, as well as duration, specificity and levels of ROS. What then are the known roles of ROS in cancer? Firstly, ROS significantly impacts cancer phenotypes. Secondly, the oxidative ROS property responsible for killing cancer cells, also impact secondary signaling networks. Thirdly, a strong correlation exist between ROS and genetic instability which may promote mutations. Finally, emerging observations suggest a role for mitochondrial ROS in cancer drug resistance, with implications for therapy. The mitochondria is a key regulator of metabolic-redox (meta-redox) alterations within cancer cells. Like a double-edged sword, mitochondrial ROS perturbations in cancer therapy may be beneficial or detrimental. However, harnessing ROS-specific cancer-targeting benefits remain a major challenge.